Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.56093/ijas.v89i11.95354
|View full text |Cite
|
Sign up to set email alerts
|

Validation of weather based forewarning model for Helicoverpa armigera in chickpea

Abstract: Weather based forewarning model for Helicoverpa armigera developed earlier was validated by recording the activity of H. armigera through pheromone trap catches in chickpea sown during rabi 2017–18 at IARI, New Delhi. The moth activity of H. armigera commenced in 52nd SMW (last week of December) and peak trap catch was during 15th SMW with 183moths/trap/week in April. The male moth population had significant positive and very strong correlation with maximum temperature (r=0.816**) and minimum temperature (r=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…The present findings are conformity with that of Yadav and Jat (2009), Kulhari and Singh (2008) and Malik et al (2015) which reported positive correlation of larval incidence with both maximum and minimum temperatures. Reddy et al (2009), Shinde et al (2013), Kachhawa et al (2016), Sagar et al (2019) and Meena et al (2023) reported positive correlation with both minimum and maximum temperatures and negative correlation with morning and afternoon relative humidity. Pandey et al (2013) noticed that the incidence increased gradually with an increase in temperature and decreased sharply with further increase in the temperature.…”
Section: Resultsmentioning
confidence: 97%
“…The present findings are conformity with that of Yadav and Jat (2009), Kulhari and Singh (2008) and Malik et al (2015) which reported positive correlation of larval incidence with both maximum and minimum temperatures. Reddy et al (2009), Shinde et al (2013), Kachhawa et al (2016), Sagar et al (2019) and Meena et al (2023) reported positive correlation with both minimum and maximum temperatures and negative correlation with morning and afternoon relative humidity. Pandey et al (2013) noticed that the incidence increased gradually with an increase in temperature and decreased sharply with further increase in the temperature.…”
Section: Resultsmentioning
confidence: 97%